2018
DOI: 10.1111/imj.13958
|View full text |Cite
|
Sign up to set email alerts
|

Clinical risk factors for acute ischaemic and haemorrhagic stroke in patients with infective endocarditis

Abstract: Among patients with IE, there exist characteristics that relate differentially to ischaemic and haemorrhagic stroke risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
4
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 44 publications
1
11
4
2
Order By: Relevance
“…Thirdly, IE patients of the later-period group developed less ischemic stroke (27.3% vs 10.3%, OR = 3.269, CI: 1.592-6.714). Previous studies reported that Staphylococcus aureus infection and vegetations on the mitral valve were risk factors for ischemic stroke [21,22] , but among the patients in this study, the later-period group showed a lower percentage of Staphylococcus aureus infection and a nonsignificant rise in patients with mitral vegetations (34.7% vs 30.9%). We speculate that an older age at onset and a higher proportion of diabetics (10.6% vs 5.2%) may play a more important role in triggering ischemic stroke.…”
Section: Clinical Featurescontrasting
confidence: 77%
“…Thirdly, IE patients of the later-period group developed less ischemic stroke (27.3% vs 10.3%, OR = 3.269, CI: 1.592-6.714). Previous studies reported that Staphylococcus aureus infection and vegetations on the mitral valve were risk factors for ischemic stroke [21,22] , but among the patients in this study, the later-period group showed a lower percentage of Staphylococcus aureus infection and a nonsignificant rise in patients with mitral vegetations (34.7% vs 30.9%). We speculate that an older age at onset and a higher proportion of diabetics (10.6% vs 5.2%) may play a more important role in triggering ischemic stroke.…”
Section: Clinical Featurescontrasting
confidence: 77%
“…Ischemic stroke is one of the most common central nervous events in IE patients, and occurred in 22% of the patients in our study, and was more common in the later-period group (27.3% vs 10.3%, P = 0.001, OR = 3.269). It has been reported that Staphylococcus aureus infection and vegetations on the mitral valve were risk factors for ischemic stroke [18,19] , but among the patients in this study, the later-period group showed a lower percentage of Staphylococcus aureus infection (20.0% vs 41.3%, P = 0.004, OR = 0.355) and a nonsignificant rise in patients with mitral vegetations (34.7% vs 30.9%).…”
Section: Discussioncontrasting
confidence: 66%
“…Staphylococcus aureus infection and vegetations on the mitral valve were risk factors for ischemic stroke [30,31] , but among the patients in this study, the later-period group showed a lower percentage of Staphylococcus aureus infection and a nonsignificant rise in patients with mitral vegetations. We speculate that an older age at onset and a higher proportion of diabetics may play a more important role in triggering ischemic stroke.…”
Section: Ie Patients Of the Later-period Group Developed Less Ischemicontrasting
confidence: 57%